Waste-to-Hydrogen pathways: Gas composition and char structure evolution during pyrolysis of food and digestate waste - Papurello, Davide; Somek, Kutlu; Zhang, Yeshui; Dionisi, Davide; Qin, Tian Heng; Wang, Tian; Lanzini, Andrea (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
This study investigates the influence of pyrolysis temperature on the yield distribution and gas composition of biochars derived from food waste (FW) and digestate waste (DW). Pyrolysis experiments were performed at 400-700 degrees C, and the resulting solid, liquid, and gas fractions were characterised. Gas compositions were quantified using Gas Chromatography (GC), while structural and physicochemical properties of the biochars were evaluated using SEM-EDS, BET, XRD, Raman spectroscopy, and TPO-DTG analysis. The proportion of syngas components, particularly hydrogen (H2), showed a pronounced dependence on temperature and feedstock type. No detectable H2 was found at 400 degrees C for either feedstock, whereas a substantial increase occurred with temperature elevation. For FW-derived gas, H2 increased from 7.41 vol% at 500 degrees C to 26.57 vol% at 700 degrees C. Similarly, DW-based gas exhibited an increase from 6.68 vol% to 18.28 vol% across the same temperature range. This rise was accompanied by a reduction in CO2 and an increase in CH4 and light hydrocarbons. Raman spectroscopy revealed a temperature-dependent structural transition, indicated by increasing ID/IG ratios from 0.57 to 0.76 in FW biochar and 0.59 to 0.67 in DW biochar, confirming enhanced disorder and defect formation, particularly in FW. Overall, the thermochemical evolution of both feedstocks demonstrates that increasing pyrolysis temperature significantly enhances hydrogen generation capacity, most notably in food waste, where H2 production increased from undetectable levels at 400 degrees C to 26.57 vol% at 700 degrees C, underscoring the strong potential of temperature-driven pathways for producing hydrogen-rich syngas from waste materials.
Keywords: Hydrogen; Biochar; Carbon; Food waste; Digestate; Pyrolysis; TEMPERATURE; COMPOUND; BIOCHARS; Chemistry; Electrochemistry; Energy & Fuels